Bilateral Ectopic Hypoplastic Uteri Attached to Bilateral Pelvic Sidewalls in a 21-Year-Old Patient with Primary Amenorrhea: The First Published Report. (31st October 2013) - Nazer, Ahmed; Abu-Zaid, Ahmed; AlOmar, Osama; Salem, Hany; Azzam, Ayman; Al-Badawi, Ismail A.
Abstract : Müllerian duct anomalies (MDAs) encompass a group of anatomical malformations resulting from defective development, fusion, migration, or resorption of Müllerian (paramesonephric) ducts during embryonic life. Herein, we report the first case of an exceedingly uncommon MDA (bilateral ectopic hypoplastic uteri attached to bilateral pelvic sidewalls) in a 21-year-old woman who was referred to our tertiary care center as a case of primary amenorrhea for workup and further management.